Modele statystyczne badań sondażowych - Ostasiewicz, Walenty (Statistical Models of Survey Research, 2007)
The paper contains the basic definitions of survey research in social sciences. The whole process of statistical modelling of social stressors is discussed in detail. Two different approaches to this kind of modelling are presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 208-229